An inkjet-printed polysaccharide matrix for on-chip sample preparation in point-of-care cell counting chambers - Zhang, Xichen; Wasserberg, Dorothee; Breukers, Christian; Connell, Bridgette J.; Schipper, Pauline J.; van Dalum, Joost; Baeten, Ellen; van den Blink, Dorine; Bloem, Andries C.; Nijhuis, Monique; Wensing, Annemarie M.J.; Terstappen, Leon W.M.M.; et al. (Royal Society of Chemistry, 2020)
On-chip sample preparation in self-contained microfluidic devices is a key element to realize simple, low-cost, yet reliablein vitrodiagnostics that can be carried out at the point-of-care (POC) with minimal training requirements by unskilled users. To address this largely unmet POC medical need, we have developed an optimized polysaccharide matrix containing the reagents which substantially improves our fully printed POC CD4 counting chambers for the monitoring of HIV patients. The simply designed counting chambers allow for capillary-driven filling with unprocessed whole blood. We carefully tailored a gellan/trehalose matrix for deposition by inkjet printing, which preserves the viability of immunostains during a shelf life of at least 3 months and enables controlled antibody release for intense and homogeneous immunofluorescent cell staining throughout the complete 60 mm2image area within 30 min. Excellent agreement between CD4 counts obtained from our fully printed CD4 counting chambers and the gold standard, flow cytometry, is demonstrated using samples both from healthy donors and HIV-infected patients.
Keywords: General Chemistry; General Chemical Engineering